Micro RNA profiles in colostrum exosomes obtained from primiparous or multiparous dairy cows - Terré, Marta; Arís, Anna; Garcia-Fruitós, Elena; Fàbregas, Francesc; Bach, Alex (Frontiers in Veterinary Science, 2024)
Colostrum is rich in membranous vesicles of endocytic origin named exosomes, with proteins, lipids, RNA, and/or DNA cargos which can play different roles in physiological processes. Like other colostrum bioactive compounds, exosomes could be also influenced by individual characteristics. The objective of the study was to characterize miRNA cargo of colostrum exosomes from primiparous and multiparous cows in different farms. Twenty-seven colostrum samples of clinically healthy Holstein cows (11 primiparous and 16 multiparous) from 3 different farms were obtained and frozen. After thawing, exosomes were isolated following an ultracentrifugation protocol, and characterized morphologically. Particle size distribution and western immunoblotting were also analyzMaed. After RNA extraction, miRNAs were sequenced and analyzed to assess potential differences in profiles between primiparous and multiparous cows from different farms. Fourteen miRNA were upregulated and 11 miRNAs downregulated in primiparous compared with multiparous cows. Most of the miRNA differences between primiparous and multiparous cows regulate the gene expression of factors involved in mammary gland development and differentiation, and lipogenesis. In addition, miRNAs from one of the farms showed 8 miRNAs downregulated and 12 upregulated compared with the other 2 farms, independently of parity. Differences in miRNA between farms were mainly associated with immune and inflammatory-related genes. In conclusion, miRNA cargos of bovine colostrum exosomes differ in primiparous and multiparous cows, and some on-farm practices might also determine the content and activity of miRNA in colostrum exosomes.